Bottom boundary layer cooling and wind‐driven upwelling enhance the catchability of spanner crab (Ranina ranina) in South‐East Queensland, Australia. (15th November 2018) - Spencer, David M.; Brown, Ian W.; Doubell, Mark J.; Brown, Christopher J.; Redondo Rodriguez, Ana; Lee, Shing Yip; Zhang, Hong; Lemckert, Charles J.
Abstract: Species catchability is an important parameter used to help optimise stock assessment modelling and the economic efficiency of commercial fishing operations. Previous studies have shown several physical oceanographic parameters, including ambient temperature, waves and currents, affect the catchability of spanner crabs ( Ranina ranina ) throughout the Indo‐Pacific. Most notably in the Australian fishery, where oceanographic processes vary over space and time, a positive relationship between bottom boundary layer temperature (BBLT) and catch rates was observed. Here, we aimed to better understand how localised oceanographic processes affected this relationship in the southernmost South‐East Queensland (SEQ) sector of the Australian fishery at seasonal and short temporal scales. Our results show cooler BBLT, upwelling‐favourable alongshore wind stress and increased catch rates occurred during mating season in austral spring. At the end of austral summer, BBLT began warming, downwelling‐favourable winds were dominant, and catch rates declined around the post‐moult period. Outputs from the generalised linear models (GLMs) that separated these effects in each season show that, at shorter temporal scales, daily catch rates also increased with episodic BBLT cooling and upwelling‐favourable alongshore wind stress, but only during austral autumn and winter. These new findings suggest that region‐specific, short‐term and seasonal variability of oceanographic processes responsible for changes in BBLT play an important role in influencing the catchability of spanner crabs. We suggest that the effects of region‐specific physical oceanographic processes must be considered in future work when investigating the catchability of commercially important fisheries species fished over large spatial domains.